2016
DOI: 10.1155/2016/5237148
|View full text |Cite
|
Sign up to set email alerts
|

L-Malate’s Plasma and Excretion Profile in the Treatment of Moderate and Severe Hemorrhagic Shock in Rats

Abstract: Introduction. Malate is a standard component in fluid therapy within a wide range of medical applications. To date, there are insufficient data regarding its plasma distribution, renal excretion, and metabolism after infusion. This study aimed to investigate these three aspects in a rat model of moderate and severe hemorrhagic shock (HS). Methods. Male Wistar rats were subjected to HS by dropping the mean arterial blood pressure to 25–30 mmHg (severe) and 40–45 mmHg (moderate), respectively, for 60 minutes. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Malic acid, in the form of its anion malate, is a trigger for the oxidation of acetyl-CoA and could increase the TCA metabolism [ 43 ]. Malate is a key anion in Jonosteril Malat (Fresenius Kabi) infusion, which is an appropriate primary fluid therapy for critical care in subjects with moderate and severe acidosis to maintain the perioperative fluid balance [ 44 ]. The intragastric administration of malate increased mitochondrial respiration and energy production in rats [ 45 ].…”
Section: Anions In Fluid Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Malic acid, in the form of its anion malate, is a trigger for the oxidation of acetyl-CoA and could increase the TCA metabolism [ 43 ]. Malate is a key anion in Jonosteril Malat (Fresenius Kabi) infusion, which is an appropriate primary fluid therapy for critical care in subjects with moderate and severe acidosis to maintain the perioperative fluid balance [ 44 ]. The intragastric administration of malate increased mitochondrial respiration and energy production in rats [ 45 ].…”
Section: Anions In Fluid Therapymentioning
confidence: 99%
“…The entire reversal of LA by an administration of regular amount of pyruvate within hours in animal models implies its great clinical significance. The comparative effects of anions in fluid therapy on LA correction are listed in Table 1 [ 28 , 31 33 , 40 42 , 44 49 , 51 53 , 57 ].…”
Section: Pyruvate As a Potential Candidate For La Correctionmentioning
confidence: 99%
“…34 In our last study, we demonstrated that only 5% of the infused malate are renally excreted, while the plasma malate concentration remained unchanged after infusion. 21 According to this, it seems likely that the vast majority of the infused malate entered the cells. Intracellular (exogenous) malate could serve as a substrate for gluconeogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…13 Malate is a citric acid cycle intermediate that exerts its positive effects in certain clinical approaches, [14][15][16][17][18] inter alia, in the treatment of HS 19,20 even though the mechanism(s) behind its positive and protective effects are not completely decoded, yet. In previous experimental studies of our group, we demonstrated that malate-containing resuscitation solutions are superior toward Ringer's solution (RS), and acetatecontaining or lactate-containing resuscitation solutions regarding median survival time and acid-base status 12,21 in the treatment of HS. Interestingly, in an experimental model of severe HS, malate rapidly disappeared from the circulation with simultaneous marginal renal excretion.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation